2015
DOI: 10.1017/dmp.2015.135
|View full text |Cite
|
Sign up to set email alerts
|

Are We Ready for Mass Fatality Incidents? Preparedness of the US Mass Fatality Infrastructure

Abstract: The sectors in the US mass fatality infrastructure report suboptimal capability to respond. National leadership is needed to ensure sector-specific and infrastructure-wide preparedness for a large-scale MFI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…In the United States, the medical examiner or the coroner typically leads the mass fatality incident response (Merrill et al , 1–10). In other countries, this may not be the case.…”
Section: Recommendationsmentioning
confidence: 99%
“…In the United States, the medical examiner or the coroner typically leads the mass fatality incident response (Merrill et al , 1–10). In other countries, this may not be the case.…”
Section: Recommendationsmentioning
confidence: 99%
“…Searchers wish for searching instruments which are precise and responsive enough to turn in results which are as relevant as possible, while excluding as many irrelevant data as possible. To this purpose, searching methods are most applicable which focus on the highest levels of sensitivity and specificity, but a low level of difference, which, however, does not eliminate the later need for discarding irrelevant results [32]. While in this study the sensitivity of PubMed search with specified tags ([sb] and [pt]) has achieved 60%, Egan et al ., [26] express that applying generic terms and consequently achieving highly sensitive searches would not result in inclusive and high quality results.…”
Section: Discussionmentioning
confidence: 89%
“…The concepts of response and preparedness are intertwined; performing preparedness measures might result in an improved response, while the experience gained from the response might bring about superior preparedness. As a result, it is probable that in articles considered by the authors to be focused on preparedness, actually the response to a disaster, the gained experience, and the disaster characteristics have been presented, or the requirements of an appropriate response may have been investigated [32]. Nevertheless, as a result of the dispersal of applicable articles, the searching process can be highly demanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a survey of mortuary operators, Gershon et al () found that most staff would need additional training, capacity, and funding to properly handle mass fatality incidents; the COVID‐19 pandemic is highlighting those needs. Merrill et al () had similar results, with survey respondents indicating that biological contaminants (such as the COVID‐19 virus) complicate their disaster response abilities. Training and resources, the ability to identify temporary burial spaces, staff health and well‐being, and public communication were additional challenges found in their study; we see many of these coming to fruition during COVID‐19 response efforts.…”
Section: Mass Casualty Events and Burial Practicesmentioning
confidence: 79%